2016
DOI: 10.4049/jimmunol.1501701
|View full text |Cite
|
Sign up to set email alerts
|

Resolvin D1 Polarizes Primary Human Macrophages toward a Proresolution Phenotype through GPR32

Abstract: Resolvin D1 (RvD1) was shown to be a potent anti-inflammatory and proresolution lipid mediator in several animal models of inflammation, but its mechanism of action in humans is not clear. We show that the RvD1 receptor GPR32 is present on resting, proinflammatory M(LPS) and alternatively activated primary human M(IL-4) macrophages, whereas TGF-β and IL-6 reduce its membrane expression. Accordingly, stimulation of resting primary human macrophages with 10 nM RvD1 for 48 h maximally reduced the secretion of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
75
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(89 citation statements)
references
References 44 publications
12
75
1
1
Order By: Relevance
“…For instance, it was recently shown that RvD1 blunts macrophage chemotaxis toward CCL2, while enhancing phagocytic function. In human macrophages, RvD1 potently blocks production of pro-inflammatory cytokines (e.g., IL-1β, IL-8 and CCL2) in a GPR32-dependent manner, which could help to prevent further recruitment of inflammatory monocytes 142 . In inflamed obese adipose tissue, RvD1 decreases the proportion of inflammatory macrophages and enhances macrophage phagocytosis and expression of arginase 1 143, 144 .…”
Section: Cellular Actions Of Resolvins In the Context Of Cvdmentioning
confidence: 99%
“…For instance, it was recently shown that RvD1 blunts macrophage chemotaxis toward CCL2, while enhancing phagocytic function. In human macrophages, RvD1 potently blocks production of pro-inflammatory cytokines (e.g., IL-1β, IL-8 and CCL2) in a GPR32-dependent manner, which could help to prevent further recruitment of inflammatory monocytes 142 . In inflamed obese adipose tissue, RvD1 decreases the proportion of inflammatory macrophages and enhances macrophage phagocytosis and expression of arginase 1 143, 144 .…”
Section: Cellular Actions Of Resolvins In the Context Of Cvdmentioning
confidence: 99%
“…RvD1 effects on macrophages seem to be transmitted by G protein-coupled receptor 32(GPR32) and the FPR2/ALX receptor [84,92,93]. …”
Section: Molecules Involved In Resolution Of Inflammationmentioning
confidence: 99%
“…29,37,38,47,49,51 Resolvins have direct actions on the recruitment and migration of neutrophils and macrophages, underlying the resolution phase of inflammation 48,5153 , and they also alter peripheral and central nervous system responses to inflammation and injury, through direct actions on neurons and glia. 65 Since the drugs that are traditionally used to treat inflammatory and post-operative pain, namely opiates and cyclo-oxygenase-2 (COX-2) inhibitors, have unwanted side effects, there is a need to find new approaches and compounds that will be more selective in their actions and have fewer adverse actions.…”
Section: Discussionmentioning
confidence: 99%
“…The primary target is one of the GPCRs known to bind resolvins; for RvD1 the receptor in rodents is ALX/FPR2 11,15,42,48 and for RvD2 the receptor is GPR18. 10 In macrophages RvD2 activation of GPR18 stimulates intracellular increases in cAMP without increasing intracellular Ca 2+ while RvD1 activation of ALX/FPR2 stimulates phosphorylation rather than increase in intracellular Ca 2+ or cAMP.…”
Section: Discussionmentioning
confidence: 99%